Systematic Literature Review (SLR): The Tradition of Dowry in Marriage in Southeast Asia - Musyaffa Amin Ash Shabah (KRTHA BHAYANGKARA, 2024)
This research aims to explore literature that examines the tradition of wedding dowries in Southeast Asia. The method used in this research is a Systematic Literature Review (SLR). Data sampling used Harzing's Publish or Perish and Watase UAKE applications starting from 2013-2023. The selected articles have passed several specified criteria, resulting in a total of 46 articles. The results of this research show that the country that discusses the topic of marriage dowry significantly in Southeast Asia is Indonesia, with a percentage of 70%, followed by Malaysia at 17%, Thailand at 7%, Vietnam at 4%, and the Philippines at 2%. In terms of research themes around wedding dowries, the topic of wedding dowry traditions is the highest topic category in research in Southeast Asia, with a total of 28 studies and a percentage of 60.87%. Likewise, the contextual approach, with a percentage of 21.74% and Fiqh Theory and Islamic Family Law, with a percentage of 10.87%, are the highest categories of research approaches and analytical theories in research on marriage dowries in Southeast Asia.